Pengaruh Beban Kerja dan Kepuasan Kerja terhadap Kinerja Pegawai Dinas Perhubungan Kabupaten Serdang Bedagai - Saragih, Sintiya L.; Tarigan, Nur M. Ridha; Elny, Sri (JRMB (Jurnal Riset Manajemen & Bisnis), 2023)
This research aims to find out how much influence the workload and job satisfaction carried out at the Serdang Bedagai Regency Transportation Service have on employee performance. This research method is quantitative and the technique used in sampling is a sampling technique where the entire population is used as a sample with a total of 79 respondents . The data source uses primary data, namely questionnaires, and secondary data obtained from interviews and literature studies. The data was processed using SPSS version 20. The data analysis technique used was multiple linear regression with the formula Y = a + b1 + X1 + b2 f test. The results of research using t statistic show that the workload variable (X1) partially has a positive and significant effect on Employee performance (Y), namely the value obtained is t-count t-table (3.545 2.213) with a significant level of 0.001 0.05 and the Job Satisfaction variable ( X2) partially has a positive but not significant effect on employee performance, namely the value of tcount ttable (2,443 2.213) with a significant level of 0.17 0.05. The results of the F test for the variables Workload (X1) and Job Satisfaction (X2) can be concluded that the variables Workload (X1) and Job Satisfaction (X2) simultaneously have a positive and significant effect on Employee Performance (Y), namely that the value Fcount Ftable ( 12,570 3.11) with a significance level of 0.01 0.05